Extracurricular physical activities and academic achievement in Saudi female physical education students: the mediating effect of motivation, enjoyment, and BMI - Frikha, Mohamed (Frontiers in Psychology, 2025)
BackgroundConsistent with the self-determination theory and the trans-contextual model of autonomous motivation in education, the present investigation aimed to analyze the relationship between extracurricular physical activity (ECPA) and academic achievement (AA), and the mediating effects of enjoyment, motivation, and BMI among Saudi female physical education (PE) students.Materials and methodsThe study followed as a descriptive cross-sectional design where a sample of 471 female PE students completed a self-administered questionnaire involving questions about their sociodemographic background, extracurricular physical activity practice, school performance, and the PE motivation and enjoyment questionnaires. Responses were collected between December 2022 and January 2023. Path analyses were chosen as a statistical method to understand the associations between the variables.ResultsThe theory-based model showed an acceptable fit with the data: (i) Standardized Root Mean Square Residual, SRMR = 0.084; (ii) comparative fit index, CFI = 0.952; (iii) Non-normed Fit Index, NNFI = 0.956; and (iv) root mean square error approximation, RMSEA = 0.051 (with CI 90%: 0.048-0.072). The Analysis revealed no significant direct effect of ECPA on AA (ß = 0.052, p > 0.05), and a significant indirect effect of enjoyment, intrinsic motivation, and BMI accounted for 20.04% of the total effect (22.9%).ConclusionThe enjoyment, intrinsic motivation, and BMI mediate the relationship between ECPA and AA in female PE students. The findings carry implications for PE teachers, principals and program makers in encouraging ECPA, supporting intrinsic motivation, enjoyment, and body image perception in Saudi female PE students.